Private Universities Survive and Thrive: From a Leadership and Human Resource Perspective - Eric Hermawan; Antoni Ludfi Arifin; Yulianto Yulianto; Taufan Maulamin; Dian Wahyudin (STAI Hubbulwathan Duri, 2023)
Private higher education institutions have encountered challenges in adapting to the dynamic landscape of change, prompting them to implement diverse tactics in order to ensure their survival. This study used a library research methodology to examine the techniques employed by private institutions in response to disruptive circumstances from leadership and human resource perspective, with a focus on their ability to adapt and thrive. The data collecting process adheres to the five stages of the historical method, which include the selection of a topic and the acquisition of relevant evidence, the examination of the sources from which the evidence is derived, the assessment of the evidence itself, the analysis and interpretation of the gathered evidence, and the presentation of the evidence together with a concluding statement. A comprehensive examination of the techniques implemented by the private university has yielded a typology consisting of four primary strategies: survival, synchronising, stretching, and supremacy. The four techniques exhibit interrelation and potential overlap in some instances. Nevertheless, survival is indicative of a strategy centred around survival. The act of stretching and synchronising contributes to the enhancement of survival and the potential for growth. Additionally, the implementation of a supremacy strategy has the ability to establish a favourable long-term image and foster positive connections with important stakeholders. These techniques have the potential to support the survival and further growth of private higher education in the current period of change.